The world of Robert Jordan's The wheel of time - Jordan, Robert, 1948-2007; Patterson, Teresa (Tor, 2021)
"Companion to The wheel of time ... series-- never-before-told legends, previously unknown peoples and lands, exotic beasts, and portents of what may come to pass"--Jacket flap.